Abstract Data Types in Modula-2 - Harrison Rachel (John Wiley & Sons, Ltd, 1989)
Current trends in Programming Methodology. Preface, Acknowledgements, Introduction, The Abstract Data Type List, The Abstract Data Type Queue, The Abstract Data Type Stack, The Abstract Data Type Set, The Abstract Data Type Tree: 1, The Abstract Data Type Tree: 2, The Abstract Data Type Table, The Abstract Data Type Graph, Bibliography, Index.